Pencegahan Paham Radikalisme Dalam Keluarga Hindu - Ni Wayan Sudarmini (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The act of radicalism is an act that disturbs and threatens the lives of others and can divide the nation. Thanotion of radicalism is a wrong understanding, because it considers soething wrong if it is not in accordance with its ideology and beliefs. From the point of view of state law and Hindusim, this has deviated from the order of relegius and state life and is contrary to the philosophy of the Indonesian nation, namely Pancasila and Bhinneka Tunggal Ika. However, radicalism group consider the ideology of the Indonesian nation inappropriate to be applied, because it is contrary to the ideology they believe in. morally and the character of the radicalism group can be said tobe immoral, because the group uses violence in realizing its wishes. Radicalism groups are also constantly lokking for follower to increase the number of their groups. The way he does it is to influence and indoctrinate others based on a certain religion. so that to be albe to preyent acts of radicalism the role of the family is needed in caring for and nurturing children. The family is the main place for children to leam be social and develop themselves. Families must build good communication and behavior from each family member. So that it will be embedded in children the values of life norms and good personalities and have character and morals thet are not easily influenced by negative things, such as radicalism.